Building Clean and Healthy Lifestyle to Prevent the Spread of Covid 19 in STM Dos Roha, Medan, Indonesia - Sismudjito; Pohan, Syafruddin; Lase, Eko Jono (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The big impact of the presence of the Covid-19 has encouraged various parties to formulate and implement optimal strategies as a preventive measures. One of them through the application of clean and healthy living habits which are allegedly relevant increasing body endurance and then pushed into this community service program. As for this activity, the aim of this activity is to build awareness of clean and healthy living habits in the community partners of the union to help Dos Roha in Dwikora Helvetia Village, Medan. Based on good search data and direct observation, the partner’s condition is very vulnerable to the dangers of Covid-19. Most partners work in the informal sector with high mobility but asymmetrical towards clean and healthy living practices and seem to ignore health protocol such as washing hands, using mask and hand-sanitizer. Move from such a condition, this community service activity is presented as a solution medium by using several implementation methods namely, 1)socialization in the form of participatory lectures, 2)experimentation in the form of environmental cooperation and disinfectant spraying, 3)stimulation in the form of giving mask, hand-sanitizer and vitamin C. The level of enthusiasm of the community in the implementation of this activity is fairly high so that this activity is very positive in changing people’s attitude towards the implementation of clean and healthy living habits.